Demographic and Competitiveness Acceleration and Government Sustainable Advantage in Indonesia - Samosir, Omas Bulan; Rajagukguk, Wilson (International Journal of Economics and Financial Issues, 2017)
The objective of this research is to investigate the effects of demographic and competitiveness acceleration on sustainable advantage in government areas in Indonesia. The research is done at district level (kabupaten/kota) in Indonesia. The sustainable advantage variable is the gross domestic product (GDP), while the demographic and competitiveness acceleration variables are the dependency ratio growth rate, capital investment, percentage share of agriculture in the economy, and percentage of women age 16 year and above with senior high school education or above. Data used cover 489 districts in Indonesia from 2008 to 2010. The data are from the Statistics Indonesia and World Bank. Data analysis using an ordinary least square regression show that to a achieve a sustainable advantage, regional management must promote the regional competitiveness acceleration by managing the dependency ratio growth rate, increasing the capital investment, reducing the share of agriculture sector in the economy and increasing women's education. Keywords: government management, competitiveness acceleration, demographic, regional, Indonesia. JEL Classifications: O18, O31